Motivating behaviour change to reduce pathogenic risk where unsafe water is used for irrigation - Karg, H.; Drechsel, Pay (Informa UK Limited, 2011)
The increased emphasis on non- or post-treatment measures in the 2006 edition of the World Health Organization Guidelines on the safe use of wastewater in agriculture will require behaviour change along the food chain. Low health risk awareness likely limits adoption of safe food practices in many areas. Based on experiences from Ghana, where informal wastewater irrigation occurs around all cities, the necessary steps for increasing adoption probability are outlined under a generic framework, which is based on the four pillars of social marketing, incentive systems, awareness creation/education and application of regulations. Any of these approaches requires research of the target groups. Cost effectiveness can be improved by linking related efforts with other hygiene and food safety interventions.